The cat who moved a mountain - Braun, Lilian Jackson (New York : Jove Books, 1992)
Jim Qwilleran and his two mystery-solving cats move to the Potato mountains and get involved in the murder of a land developer.
Booklist.
Library Journal.
Wilson's Fiction.
Young Adult
Keywords: Cats -- Fiction; Journalists -- United States -- Fiction; Qwilleran, Jim (Fictitious character) -- Fiction; Cats -- Fiction; Journalists -- Fiction; Mystery fiction; Qwilleran, Jim (Fictional character) -- Fiction; Detective and mystery stories